2022
DOI: 10.1002/ibra.12026
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of the CXCR4 mechanism in Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a degenerative brain disease with complex clinical manifestations and pathogeneses such as abnormal deposition of beta-amyloid protein and inflammation caused by the excessive activation of microglia. CXC motif chemokine receptor type 4 (CXCR4) is a type of G protein-coupled receptor that binds to CXC motif ligand 12 (CXCL12) to activate downstream signaling pathways, such as the Janus kinase/signal transducer and activator of transcription and the renin-angiotensin system (Ras)/RAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Increased plasma level of GFAP is also suggested as a potential prognostic marker in COVID-19, associated with mortality risk [81]. CXCR4 is another up-regulated hub gene in AD and COVID-19 patients [82,83]. CXCR4 is a G protein coupled receptor that binds to CXCL12 and triggers downstream signaling pathways associated with inflammatory pathways [82].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased plasma level of GFAP is also suggested as a potential prognostic marker in COVID-19, associated with mortality risk [81]. CXCR4 is another up-regulated hub gene in AD and COVID-19 patients [82,83]. CXCR4 is a G protein coupled receptor that binds to CXCL12 and triggers downstream signaling pathways associated with inflammatory pathways [82].…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 is another up-regulated hub gene in AD and COVID-19 patients [82,83]. CXCR4 is a G protein coupled receptor that binds to CXCL12 and triggers downstream signaling pathways associated with inflammatory pathways [82]. CXCR4 is involved in neuronal guidance and apoptosis via astroglial signaling and microglial activation [84].…”
Section: Discussionmentioning
confidence: 99%
“…These clues support the synapse, a key site where the functional connection between neurons occurs ( Faria-Pereira and Morais, 2022 ), whose information transmission was in chaos post infection. Alterations in synaptic signaling, in the release of neurotransmitters from presynaptic neurons, changes in binding to postsynaptic receptors, and synaptic degeneration are evident in the course of many neurodegenerative diseases ( Parmar et al., 2022 ; Peng et al., 2022 ; Wang et al., 2022a ). Indeed, we found that several differentially expressed proteins were involved in the pathways of KEGG associated with neurodegenerative diseases, autophagy, and other signaling.…”
Section: Discussionmentioning
confidence: 99%
“…AD is a CNS degenerative disease characterized by pathological changes of cortical and hippocampal neuron loss, amyloid β‐protein (Aβ) aggregation‐formed plaques, and tau protein hyperphosphorylation‐induced neurofibrillary tangles, which is clinically manifested by progressive cognitive impairment, especially memory (Spence et al, 2017; Wang et al, 2022). Therefore, reducing the accumulation of Aβ in the brain and protecting neurons may become an effective way in the prevention and treatment of AD.…”
Section: The Regulatory Potentials Of P75ntr In Neurological Diseasesmentioning
confidence: 99%